2021
DOI: 10.3390/app11115145
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Long-Term Performances of SMA-13 Containing Different Fibers

Abstract: To clarify the influence of fiber type on the long-term performance of stone mastic asphalt (SMA), this paper used basalt fiber (BF) and lignin fiber (LF) to modify SMA-13 (SMA with aggregate nominal maximum particle size of 13.2 mm) asphalt mixture. The pavement performances (high-temperature performance, cracking resistance at low and medium temperature, and water stability) of the two kinds of fiber-reinforced SMA-13 were checked under different aging degrees (unaged, short-term aged and long-term aged), sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Long-life pavement has been a hot topic, so the long-term performance study of fiber-reinforced asphalt pavement deserves attention, and obviously, there is less research in this area. By wheel tracking test and uniaxial penetration test, Wu et al [ 72 ] found that the high temperature performance of BF SMA-13 improved with increasing aging, while the aging process of lignin SMA-13 reduced its high-temperature performance. This is because in BF SMA-13, although SBS degradation also leads to a decrease in the high-temperature performance of the asphalt mix, the BFs work better synergistically with the stiffer binder, which ultimately leads to an improvement in the high temperature performance of the asphalt mix.…”
Section: Performance Of Asphalt Mixture Modified With Basalt Fibermentioning
confidence: 99%
“…Long-life pavement has been a hot topic, so the long-term performance study of fiber-reinforced asphalt pavement deserves attention, and obviously, there is less research in this area. By wheel tracking test and uniaxial penetration test, Wu et al [ 72 ] found that the high temperature performance of BF SMA-13 improved with increasing aging, while the aging process of lignin SMA-13 reduced its high-temperature performance. This is because in BF SMA-13, although SBS degradation also leads to a decrease in the high-temperature performance of the asphalt mix, the BFs work better synergistically with the stiffer binder, which ultimately leads to an improvement in the high temperature performance of the asphalt mix.…”
Section: Performance Of Asphalt Mixture Modified With Basalt Fibermentioning
confidence: 99%
“…e semicircular bending (SCB) test was used to evaluate the low-temperature crack resistance of asphalt mixtures. e fracture energy (G) was calculated as the evaluation index [25,26]. e setup for the SCB test consists of a loading ramp at the top center of the sample and two supporting rollers at two sides of the bottom, with a distance of 80 mm, as shown in Figure 6.…”
Section: Semicircular Bendingmentioning
confidence: 99%
“…Fibers and polymers are the two main admixtures for asphalt mixtures. Fibers have already been applied for asphalt mixtures for more than 50 years [4]. After the 1990s, with the use of stone mastic asphalt (SMA) in pavements, more fibers were adopted in asphalt mixtures [3], such as synthetic fibers [5], kenaf fiber [6], glass fiber [7], etc.…”
Section: Introductionmentioning
confidence: 99%